Warnings of financial fraud in travel agencies in the Republic of Serbia during the COVID-19 pandemic - Dimitrijević, Dragomir; Stanković, Predrag; Vržina, Stefan (Hotel and Tourism Management, 2024)
Purpose – The purpose of this paper is to determine the change in warning signs of fraud in the financial reports of travel agencies during the COVID-19 pandemic compared to the pre-pandemic period and to investigate a potential increase in the risk of bankruptcy in travel agencies during the same period. Methodology – The methodology used in the research comprises the analytical methods of forensic accounting (Beneish model and Altman Z-score), as well as descriptive statistics. Findings – The results of the research show that there is a certain increase in warning signs during the pandemic compared to the period before the pandemic and there the risk of bankruptcy in travel agencies increases during the pandemic. Implications – The theoretical implications of the study relate to expanding our knowledge about the importance of analytical techniques of forensic accounting and quantifying the probability of manipulation in the travel agencies’ financial reports. The practical implications of the work relate to the usefulness of the results for authorized fraud investigators as well as for investors in travel agencies. On the other hand, the results can be useful for clients of travel agencies when selecting travel agencies.